A Community Service Project at SD 4 Lenek to Improve School Buildings and Raise Awareness about K3 Occupational Safety - Fera Fitri Salsabila; Dewandha Mas Agastya; Pathurahman; I Nyoman Merdana; Evrianti Syntia Dewi; Rohani; I Dewa Made Alit Karyawan; Hasyim; Ratna Yuniarti; Desi Widianty; Ida Ayu Oka Suwati Sideman; I Wayan Suteja; Made Mahendra (Unram Journal of Community Service, 2025)
School safety and how well buildings work are very important for creating good learning environments, especially in rural areas.  The goal of this community service program was to make SD 4 Lenek, East Lombok, a safer place for students by (1) fixing up the school buildings and (2) raising awareness about Occupational Safety and Health (K3) among teachers, staff, and students.  The activities included checking the facilities, making small repairs to the building, putting up safety signs, making evacuation routes, and an interactive K3 seminar given by the authors as guest speakers.  The evaluation results showed that building safety indicators had gotten better and that K3 knowledge among school stakeholders had grown. This was shown by a big jump in post-test scores.  This program stresses that combining physical revitalization with safety education is very important for making schools safer.